AB0542 PREGNANCY OUTCOMES IN ANTIPHOSPHOLIPID SYNDROME: 8 YEAR-EXPERIENCE FROM A MULTIDISCIPLINARY UNIT. (June 2019) - Neto, Agna; Martins, Patrícia; Capela, Susana; Araujo, Claudia; Centeno, Mónica; Costa, Manuela; Pinto, Luísa
Abstract : Background: Women with antiphospholipid syndrome (APS) are at increased risk of recurrent miscarriage, fetal death, placental insufficiency, preeclampsia and fetal growth restriction. Although treatment improves fetal-maternal outcomes, there are still some unsuccessful pregnancies. A multidisciplinary approach with strict monitoring is essential in order to attain obstetrical success. Objectives: To assess pregnancy outcomes in portuguese women with APS who were surveilled at a multidisciplinary unit. Methods: Pregnant women fulfilling the Sydney classification criteria for definite APS, who attended our specialized Rheumatology and Obstetrics outpatient clinic between 2010 and 2018, were included in this retrospective observational study. Cases of suspected APS not meeting the classification criteria were excluded. All pregnancies were followed by a multidisciplinary team (rheumatologists, obstetricians and nurses). Data was collected from medical records. Adverse Pregnancy Outcomes (APO) were defined as: spontaneous abortion (<10w), fetal death (≥10w), neonatal death, fetal growth restriction (FGR) and delivery prior to 36 weeks of gestation with or without preeclampsia (PE). Results: A total of 35 pregnancies were identified in 25 women with APS. Twelve (48%) patients had thrombotic APS, 9 (36%) had obstetric APS and 4 (16%) had mixed APS. Primary APS was seen in 56% of patients, while systemic lupus erythematosus was found in 44%. The average maternal age at conception was 32.8 ± 5.2 years. Mean duration of disease prior to pregnancy was 6.4 ± 5.5 years. In regard to antiphospholipid antibody (APL) profile, 28.6%, 25.7% and 28.6% of patients were triple, double and single positive, respectively. Although they had fulfilled laboratorial criteria in the past, 17% of patients were negative for all APL. All patients were instructed to receive prophylactic or therapeutic low-molecular-weight heparin combined with low dose aspirin for the duration of pregnancy. Regarding fetal outcomes, there were 2 (5.7%) cases of first-trimester miscarriage, 1 (2.9%) medical abortion due to exposure to teratogenic drugs at the time of conception and 4 (11.4%) fetal deaths. Among the cases of fetal death, one concerned a patient who suspended heparin on her own initiative and another one who became pregnant under warfarin and whose fetus had trisomy 18. The other cases occurred at 11 and 18 weeks of gestation, under regular therapy. There were no cases of neonatal death or other fetal malformations. The rate of live births was 80%, with a mean gestational age of 37.3 ± 1.5 weeks and mean birth weight of 2796.4 ± 462 g. Most women delivered by cesarean section (54.3% of cases). There were 6 (17.1%) cases of preterm birth, three (8.6%) corresponding to fetus with FGR. Concerning maternal outcomes, there was one single case (2.9%) of PE. There were no cases of eclampsia or HELLP syndrome. Lupus anticoagulant ( p = 0.003, OR 25, CI 95% 1.32 – 474.0) and triple APL ( p = 0.045, OR 5.7, CI 95% 1.15 – 28.33) positivity were associated with adverse pregnancy outcomes. In this cohort, no association was found between poor obstetric outcomes and history of thrombosis, presence of SLE or low complement levels (table 1 ). Conclusion: In our study, most pregnancies were uneventful. Despite the small sample size, we reinforce the importance of a multidisciplinary evaluation and surveillance before, during and after pregnancy in women with APS in order to implement early treatment and to optimize fetal-maternal outcomes. Disclosure of Interests: None declared